STUDI TENTANG BENTUK DAN CIRI KHAS SOUVENIR DARI KAYU SEBAGAI PENUNJANG PARIWISATA BUKITTINGGI - Vero Mario, Drs. Efrizal, M.Pd, Dra. Zubaidah, M.Pd (Serupa The Journal of Art Education, 2013)
This study purpose has to describe 1) the form of souvenirs that there di Pasa Ateh Bukittinggi, 2) charaktersistic of souvenirs from wood in Pasa Ateh Bukittinggi 3) notice of tourists on wooden souvenirs in the Pasa Ateh Bukittinggi. This study used qualitative methods. Sources of data in this study is primary data, in the form of oral testimony of artisans and merchants, secondary data from literature. The procedures data collection with observation, interviews, and documentation. Data analysis was performed with data reduction, data display (presentation of data), and draw conclusions. Checking the validity of the used the triangulation technique. Results of reseach that found shape and characteristic souvenirs Minangkabau and not characteristic souvenirs Minangkabau. Kata Kunci: souvenir dari kayu, pariwisata di Pasa Ateh Bukittinggi.